Person and the syntax–discourse interface: An eye-tracking study of agreement - Mancini, Simona; Molinaro, Nicola; Davidson, Doug J.; Avilés, Alberto; Carreiras, Manuel (Journal of memory and language, 2014)
•We investigated the role of morphosyntax and discourse in agreement comprehension.•We compared unagreement, standard agreement, null-subject and incorrect sentences.•One grammatical judgment task and three eye-tracking experiments were used.•Morphosyntactic checking between subject and verb guides initial stages of processing.•Discourse-related analysis takes place in later phases of agreement processing. The time-course of agreement processing was investigated through three eye-tracking experiments and one grammaticality judgment task by making use of the Spanish Unagreement pattern, which allows the presence of a 3rd person plural subject followed by a 1st person plural verb, as in Los manifestantes anunciamos una huelga (The protesters3.pl announced1.pl a strike). Grammaticality is ensured by re-interpreting the subject as 1st person plural, thereby changing the underlying discourse composition of the sentence (We protesters announced a strike). The comparison of Unagreement with structurally similar sentences (Experiment 1), truly person-anomalous sentences (Experiments 2 and 3) and discourse-incongruent sentences (Experiment 4) revealed a clear dissociation between morphosyntactic-related and discourse-related analysis in agreement comprehension. The constant first-pass effect elicited by Unagreement with respect to structurally similar (grammatical and ungrammatical) sentences across the four experiments evidences the sensitivity of early stages to morphosyntactic evaluation, while the differential effect for discourse-congruous and discourse-incongruous sentences in later measures suggests that discourse-related analyses are dealt with by the parser in subsequent stages of processing.